Association between balance and hip muscle strength in inline skaters - Torres, L. S.; Moltó, I. N.; Navia, J. A., Abellán, J. R. (Journal of Functional Morphology and Kinesiology, 2025)
Background: Inline skating has rapidly grown in popularity. Early research primarily focused on injury patterns and protective measures. However, its biomechanical similarity to other skating modalities enables the synthesis of existing evidence, emphasizing key physical attributes essential for performance, namely, balance and the strength of the hip adductor and abductor muscles. The interaction between these muscle groups in relation to balance has not yet been examined in inline skaters. This study aimed to investigate the relationship between single-leg static balance and the isometric strength of the hip adductors and abductors, including their strength ratio.